2014
DOI: 10.1633/jistap.2014.2.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access and Use among Students of Physical Education: A Study of Kurukshetra University, Kurukshetra

Abstract: This paper depicts a study conducted on the behavior of physical education students towards Internet usage at Kurukshetra University, Kurukshetra. Specially, the study aims to know the purposes for use of Internet resources and services, frequency of use, places and means of use, student's satisfaction level toward the Internet, and problems faced while using the Internet. A survey was carried out with a sample of 100 physical education students of Kurukshetra University and the response rate was 88%. A well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…Other barriers stated by very few students were Internet data packets exhausting, internet networks disturbing, and annoying advertisements on the internet. This finding is different with Kumar (2014) who revealed that the most problem encountered by physics education students at Kurukshetra University was too much information on the internet (61.4%). About the internet speed barrier, only 56.8% of students experienced it.…”
Section: Purposes and Barriers In Accessing The Internetcontrasting
confidence: 85%
See 1 more Smart Citation
“…Other barriers stated by very few students were Internet data packets exhausting, internet networks disturbing, and annoying advertisements on the internet. This finding is different with Kumar (2014) who revealed that the most problem encountered by physics education students at Kurukshetra University was too much information on the internet (61.4%). About the internet speed barrier, only 56.8% of students experienced it.…”
Section: Purposes and Barriers In Accessing The Internetcontrasting
confidence: 85%
“…The instrument employed in this research consisted of a questionnaire and two scales. The questionnaire was partially adopted from Loan (2011), Gökalp (2013), and Kumar (2014). It was used to collect data of students' demographic profiles, computer and internet facilities, experience and frequency of accessing internet, purpose of using the internet in general and in physics learning, and barriers in accessing the internet.…”
Section: Methodsmentioning
confidence: 99%
“…User behavior in academic libraries has changed significantly over the past decade, and most libraries now follow Web enabled OPAC rather than a traditional catalogue. Kumar (2017) in his study tries to determine the awareness and usage of OPAC among English, Mathematics and Commerce students of Kurukshetra University, Haryana. The study reveals that students' knowledge of OPAC is weak, and most students use the OPAC to search for documents from the shelves using the Title search (33.90%) with the assistance of library staff.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…As Internet evolution has also affected the modern education system without a doubt, and 21st-century students, known as the Internet generation students, are showing great interest in growing educational proficiency. In the web world, it is possible to access all over the world at once with one click on devices connected to the internet [21], [22].…”
Section: Introductionmentioning
confidence: 99%